(G'/G)-Expansion method for (3+1)-dimensional burgers and burgers like equations - Duran, Serbay; Ugurlu, Yavuz; Enam Inan, Ibrahim (My University, 2012)
In this paper, we implemented the (G'/G)-expansion method the traveling wave solutions of the Burgers-like equation and (3+1)-dimensional Burgers equation. By using this scheme, we found some traveling wave solutions of the above-mentioned equations. © IDOSI Publications, 2012.
Keywords: (3+1)-dimensional burgers equation; (G'/G)-expansion method; Burgers-like equation; Nonlinear equations; Traveling wave solutions